Miri City as a festival destination image in the context of Miri Country Music Festival - Sia, Joseph; Lew, Tek Yew; Sim, A. (Elsevier BV, 2015)
The primary objective of the study is to ascertain the festival destination image of Miri. More specifically the study objectives are to determine Miri as a festival destination image among the tourists in the context of Miri Country Music Festival (MCMF) and to assess tourist’s satisfaction level of MCMF. The findings show that the participants have positive impression about Miri being a festival destination image. This paper provides some insights to relevant authorities for further improvements to meet the expectation of the tourists. The limitations of the study and future research are also discussed in this paper.